Cell Wall Glucans of the Yeast and Mycelial Forms of Paracoccidioides brasiliensis - Kanetsuna, Fuminori (1970)
Glucans were isolated from the cell wall of the yeast (Y) and mycelial (M) forms of Paracoccidioides brasiliensis. The alkali-soluble glucan of the Y form had properties of α-1,3-glucan. The alkali-insoluble glucan of the M form was identified as a β-glucan which contains a β-(1 → 3)-glycosidic linkage by infrared absorption spectrum, by effect of β-1,3-glucanase, and by partial acid hydrolysis. The alkali-soluble glucans of the M form were a mixture of α- and β-glucans and the ratio of α- to β-glucan was variable, depending on the preparations.